Type 1 Kounis Syndrome in Patient with Idiopathic Anaphylaxis - Tajda Keber; Jana Makuc; Gregor Sekavčnik (Case Reports in Cardiology)
Kounis syndrome represents the concurrence of acute coronary syndromes or anginal pain with allergic, hypersensitivity, and anaphylactic reactions. It can be associated with normal coronary angiogram or preexistent coronary pathology. Idiopathic anaphylaxis is defined as anaphylaxis without any identifiable precipitating agent or event. We present a case of male who experienced attacks of dyspnoea, hypoxemia, hypotension, purple-red skin, and chest pain over several years. He was diagnosed with idiopathic anaphylaxis. Based on the pattern of chest pain of ischemic origin during the attacks he was retrospectively diagnosed with Kounis syndrome.